Effects of a novel fermented soy product on the serum lipids of hypercholesterolemic rabbits - Rossi, Elizeu Antonio [UNESP]; Vendramini, Regina Célia [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Ueiji, Igor S. [UNESP]; Squinzari, Márcio M. [UNESP]; Silva Jr, Sinézio I. [UNESP]; Valdez, Graciela F. [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2000)
OBJECTIVE: To assess the effect of a new feed soy product fermented by Enterococcus faecium and Lactobacillus jugurti on the serum lipid levels of rabbits with induced hypercholesterolemia. METHODS: Thirty-two rabbits were divided into 4 groups as follows: 1) control (C); 2) hypercholesterolemic (H); 3) hypercholesterolemic + fermented product (HPF); and 4) control + fermented product (CPF). The H and HPF groups were fed with a diet with 0.15% (p/p) cholesterol in the first 15 days. C and CPF groups received regular food preparation. The HPF and CPF groups received 10 mL daily of the fermented 30 days. Blood samples were drawn at the beginning of the study and at the 15th and 30th days. Concentrations of total cholesterol, HDL-cholesterol, and triglycerides were analyzed. RESULTS: After 15 days, the HPF group showed a total cholesterol concentration lower (18.4%) than that of the H group (p=0.05), but this difference disappeared after 30 days. No change was observed in total cholesterol levels of C and CPF groups. After 15 days, the HDL-cholesterol was higher (17.8%) in the HPF group, but the triglyceride levels remained unchanged in all groups during the same period of time. CONCLUSION: The soy fermented product caused an 18.4% reduction in total cholesterol and a 17.8% increase in the HDL-fraction. It may, therefore, be a possible coadjutor in the treatment of hypercholesterolemia.
Keywords: fermented soy product; Enterococcus faecium; cholesterol